Database of metal concentrations measured in sediment cores (1965-2011) and bed and flood sediments (1987-2018) along the Rhône River - André-Marie Dendievel; Jean-Philippe Bedell; Sidonie Cayambo; Myriam Hamada; Yohan Liber; Mansuy Thomas; Brice Mourier (PANGAEA, 2020)
This database contains metal element concentrations from (1) river sediment cores and (2) bed and flood deposits acquired along the Rhône River by research teams (for 1: LEHNA-IPE) and monitoring programmes (for 2 : RMC Water Agency). This dataset focuses on six areas (geographical clusters: GC-1 to GC-6) located along the Rhône River corridor (ca. 512 km), after its confluence with the Arve River (near Geneva in Switzerland) to its delta near Arles (France). It presents the variations of metal concentrations for the following elements: Al, Fe, Cd, Cr, Cu, Ni, Pb, Zn during the period 1965-2018. It also includes the geo-accumulation values (Igeo) and enrichment factors (EFs) for Cd, Cr, Cu, Ni, Pb, and Zn. Extraction techniques (Aqua Regia or Total Extraction) and ancillary data such as total organic carbon content (TOC in % - pct), grainsize (fine fraction proportion: clay and silts < 63 μm), distance upstream of estuarine area (km UEA), sampling depth and date or expected age (for river sediment cores) are also reported.